miekka; kaksiteräinen miekka
physical description: A fragmentary sword in fair condition and lacking its pommel. Weight: 868 g. On one side the fuller has a woven lattice and six vertical lines, and the reverse side contains fragmentary marks, which could indicate an ULFBERHT inscription. The material of the inlays seems to be non-twisted pattern-welded rod, or strongly corroded iron or steel containing a great deal of impurities. The inlays were defined with the aid of radiograph no. 2599.